2006
DOI: 10.1177/0734282906287830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Instructions on Curriculum-Based Measurement of Reading

Abstract: The aim of this study was to investigate the effect of instructions of curriculum-based measurement (CBM) of reading on (a) the number of words read correctly and incorrectly per minute and (b) the relationship between CBM reading and reading achievement. Results indicated that the specific instructions used have a significant impact on CBM reading outcomes. Statistically significant mean differences were found among the fast, best, and baseline reading conditions in the number of words read correctly and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…In this regard it is also important to note that when testing for reading fluency, the nature of the instructions might affect the results. Instructions of the kind given in this study to read ''as fast as you can'' have been shown to affect participants' performance as they are less likely to focus on accuracy or meaning (Colón & Kranzler, 2006). In addition, reading development in ELL populations can be the result of a complex interaction of linguistic and cultural factors which may impede second language development.…”
Section: Discussionmentioning
confidence: 96%
“…In this regard it is also important to note that when testing for reading fluency, the nature of the instructions might affect the results. Instructions of the kind given in this study to read ''as fast as you can'' have been shown to affect participants' performance as they are less likely to focus on accuracy or meaning (Colón & Kranzler, 2006). In addition, reading development in ELL populations can be the result of a complex interaction of linguistic and cultural factors which may impede second language development.…”
Section: Discussionmentioning
confidence: 96%
“…Differences in WRCM scores across time are not solely attributable to meaningful changes in oral reading rate. The manner in which probes are constructed (Christ & Ardoin, 2009; Hintze & Christ, 2004), differences in difficulty among passage sets (Betts, Pickart, & Heistad, 2009; Cummings, Park, & Bauer Schaper, 2013; Francis et al, 2009), the type of passage (e.g., expository vs. narrative; O’Keeffe, Bundock, Kladis, Yan, & Nelson, 2017), the manner in which instructions are delivered (Christ, White, Ardoin, & Eckert, 2013; Colon & Kranzler, 2006), the setting in which data are collected (Derr & Shapiro, 1989), and errors committed by data collectors (Cummings, Biancarosa, Schaper, & Reed, 2014) all influence the observed WRCM for a student at any given point in time. Further, it is likely that idiosyncratic differences in the testing environment and disposition of the student may contribute to minor fluctuations in performance.…”
Section: Cbm-rmentioning
confidence: 99%
“…WCPM data have been shown to be sensitive to a variety of extraneous variables, including testing conditions, directions, probe difficulty levels, and administration and scoring errors (Colón & Kranzler, 2006;Derr-Minneci & Shapiro, 1992;Hintze & Christ, 2004;Poncy et al, 2005). Derr-Minneci and Shapiro (1992) found that numerous testing conditions, including who administered the test (teacher or psychologist), where it was given (teacher's desk or psychologist's office), and the task demand (timed and untimed probes) influenced WCPM scores.…”
Section: Sensitivity: a Double-edged Sword Of Rate-based Measuresmentioning
confidence: 99%
“…Derr‐Minneci and Shapiro () found that numerous testing conditions, including who administered the test (teacher or psychologist), where it was given (teacher's desk or psychologist's office), and the task demand (timed and untimed probes) influenced WCPM scores. Colón and Kranzler () changed one sentence in the administration directions from “Do your best reading” to “Read as fast as you can without making mistakes” and found an average increase of 36 WCPM in fifth‐grade students, an alarming finding considering that Ardoin and Christ () found that fifth‐grade students grew an average of 32 to 33 WCPM over the course of a year. Poncy et al () found that 81% of the variability in WCPM scores was due to student skill, whereas 10% of the variability was due to the unequal passage difficulty of the probes utilized.…”
Section: Better Measures Of Behavior Change: the Vertical Axismentioning
confidence: 99%